Snow and ice control manual for transportation facilities - Minsk, L.D. (L. David) (Construction series (McGraw-Hill, inc.), 1998)
Technology of snow and ice control has changed considerably in the last decade, with the development of many cost saving techniques, equipment, and materials. Environmental concerns have forced a rethinking of old techniques and this book provides a detailed source of information on the subject.